The Impact of Auditory Spectral Resolution on Listening Effort Revealed by Pupil Dilation. Issue 4 (July 2015) - Winn, Matthew B.; Edwards, Jan R.; Litovsky, Ruth Y.
Abstract : Objectives: This study measured the impact of auditory spectral resolution on listening effort. Systematic degradation in spectral resolution was hypothesized to elicit corresponding systematic increases in pupil dilation, consistent with the notion of pupil dilation as a marker of cognitive load. Design: Spectral resolution of sentences was varied with two different vocoders: (1) a noise-channel vocoder with a variable number of spectral channels; and (2) a vocoder designed to simulate front-end processing of a cochlear implant, including peak-picking channel selection with variable synthesis filter slopes to simulate spread of neural excitation. Pupil dilation was measured after subject-specific luminance adjustment and trial-specific baseline measures. Mixed-effects growth curve analysis was used to model pupillary responses over time. Results: For both types of vocoder, pupil dilation grew with each successive degradation in spectral resolution. Within each condition, pupillary responses were not related to intelligibility scores, and the effect of spectral resolution on pupil dilation persisted even when only analyzing trials in which responses were 100% correct. Conclusions: Intelligibility scores alone were not sufficient to quantify the effort required to understand speech with poor resolution. Degraded spectral resolution results in increased effort required to understand speech, even when intelligibility is at 100%. Pupillary responses were a sensitive and highly granular measurement to reveal changes in listening effort. Pupillary responses might potentially reveal the benefits of aural prostheses that are not captured by speech intelligibility performance alone as well as the disadvantages that are overcome by increased listening effort. Abstract : Elevated listening effort is a significant problem for people with hearing impairment. In this study, pupillometry was used to measure listening effort in listeners with normal hearing who heard speech signals that were degraded to simulate a cochlear implant. For each successive degradation in spectral resolution, there was a corresponding increase in the pupillary response, suggesting greater effort needed to perceive spectrally degraded speech. Speech intelligibility scores were not predictive of listening effort, underscoring the need for sensitive tools to reveal differences in performance that are not captured by conventional testing methods.Supplemental Digital Content is available in the text.